Investigating Growth of Gold Nanorods by Simultaneous Small‐Angle X‐Ray and Neutron Scattering. (7th February 2022) - Zech, Tobias; Metwalli, Ezzeldin; Götz, Klaus; Schuldes, Isabel; Porcar, Lionel; Unruh, Tobias
Abstract : Increased usage of gold nanorods (AuNRs) in various biosensing and medical applications requires tight size and morphology control. This is often achieved by tuning the aggregation behavior of the stabilizing ligand cetrimonium bromide (CTAB). Because the role of CTAB during AuNR growth is still a matter of debate, simultaneous small‐angle X‐ray and neutron scattering experiments (SAXS/SANS) and measurements are performed. The SAXS/SANS measurements have enabled an instantaneous correlation between the size of evolving AuNR and the nanostructure of guiding CTAB moieties. Upon modifying the aggregation behavior of CTAB micelles by adding hexanol or pentanol as inert additives in the precursor solution, a marked change in reaction kinetics is observed. Alcohol‐modified CTAB nanostructures have improved AuNR size uniformity compared to those prepared in alcohol‐free CTAB solutions, which are attributed to different growth modes. The change in reaction kinetics is linked to a changed stabilization mechanism of reactants and nascent AuNR facilitated by CTAB micelles. Abstract : T. Zech, E. Metwalli, K. Götz, I. Schuldes, L. Porcar, T. Unruh The scattering signal of cetrimonium bromide (CTAB) structures and gold nanorods (AuNRs) is measured and correlated directly by simultaneously impinging the sample volume with X‐rays and neutrons. Insight into the growth kinetics of AuNR is gained by modifying the CTAB structures with short‐chained alcohols. The influence of stabilizing CTAB structures on AuNR growth kinetics, polydispersity, and morphology changes are discussed.